PO236 A rare encounter with a common condition: encephalopathy in a tourist. (1st December 2017) - O'Malley, Ronan; Majid, Arshad
Abstract : A 24 year old lady with a background of an arteriovenous malformation treated with the Gamma Knife. She had travelled extensively throughout South East Asia before becoming unwell. There was a prodrome of hallucinations and altered behaviour before a marked reduction in GCS, high fever and subsequent seizures. The initial differential included meningitis, encephalitis, carbon monoxide poisoning and illicit drug abuse.The patient underwent extensive investigation and, despite treatment with anti-epileptics, antibiotics and anti-virals, failed to improve. She remained in a continuous vegetative state for a protracted period with brain imaging reflecting extensive damage to the basal ganglia. The examination was characterised by flaccid upper limbs and spastic lower limbs, in the absence of any apparent spinal pathology. Japanese Encephalitis (JEV) PCR was negative when tested in S.E Asia and was negative. Subsequent serology was positive, which along with the clinical ad radiological features led to the diagnosis of JEV The patient has improved to the point of being aware and responding to environmental stimuli. She remains ventilator dependent. This illuminating case posed both a challenge with regards to both diagnosis and management. Whilst relatively prevalent in endemic areas, few British Neurologists are likely to have encountered this condition.